2017
DOI: 10.1002/cncr.30771
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Medicaid disenrollment in Tennessee on breast cancer stage at diagnosis and treatment

Abstract: The results of the current study indicate that Medicaid disenrollment is associated with a later stage of disease at the time of breast cancer diagnosis, thereby providing evidence of the potential negative health impacts of Medicaid contractions. Cancer 2017;123:3312-9. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
(34 reference statements)
2
19
0
Order By: Relevance
“…Our present study confirms delays to surgery and radiotherapy, but no delays between surgery and chemotherapy 6 . This is in contrast to the effect of the 2005 Medicaid disenrollment in Tennessee, which resulted in the later stage of disease at diagnosis of breast cancer and decreased delays to treatment 12 . As studies continue to evaluate the complex interactions between healthcare reform and cancer care, 13 we have attempted to understand other factors related to treatment delays.…”
Section: Discussionsupporting
confidence: 79%
“…Our present study confirms delays to surgery and radiotherapy, but no delays between surgery and chemotherapy 6 . This is in contrast to the effect of the 2005 Medicaid disenrollment in Tennessee, which resulted in the later stage of disease at diagnosis of breast cancer and decreased delays to treatment 12 . As studies continue to evaluate the complex interactions between healthcare reform and cancer care, 13 we have attempted to understand other factors related to treatment delays.…”
Section: Discussionsupporting
confidence: 79%
“…Tennessee in the mid–2000 s had the largest contraction of its Medicaid program in its history due to budgetary challenges [10,11]. A new paper published on breast cancer outcomes in Tennessee post Medicaid contraction indicates that post contraction of the Tennessee Medicaid program, there were increases in delays in accessing treatment and an increase in later stage of diagnosis for breast cancer [12]. Further study is needed to examine how closely the regional variations in disparity correlate with variations in provision of health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Cancer , Tarazi et al investigated the effects of a state policy that substantially limited Medicaid enrollment on the timeliness of breast cancer diagnosis. In 2005, Tennessee, which previously had provided coverage to individuals with incomes up to 400% of the FPL, adopted reduced income threshold levels consistent with traditional Medicaid coverage, resulting in the abrupt disenrollment of approximately 170,000 low‐income beneficiaries .…”
mentioning
confidence: 99%
“…Surprisingly, Tarazi et al found that Tennessee's Medicaid disenrollment resulted in a statistically significant lower rate (1.9 percentage points) of surgical delays of >60 days for women living in low‐income areas compared with women living in high‐income areas . Women in both income groups experienced more surgical delays after the policy change, but the increase was greater for women in high‐income areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation